Pengaruh Citra Merek, Fitur, Dan Persepsi Harga Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Smartphone Xiaomi) di Kabupaten Lamongan - Ahmad Firhan Ah’sani; Hadi Purnomo (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This study aims to determine the effect of brand image, features, and price perceptions on purchasing decisions with a case study on Xiaomi smartphone consumers in Lamongan Regency. The research method used is a quantitative method with primary data through questionnaires distributed to respondents. The sampling technique in this study is the Accidental Sampling technique, which is a sampling technique based on coincidence, namely consumers who coincidentally/incidentally meet with researchers in the population, which then obtained 96 samples. The results obtained from the research conducted indicate that brand image has a negative effect on purchasing decisions, this is inversely proportional to other results that features have a positive effect on purchasing decisions, price perceptions have a positive effect on purchasing decisions. price perception has a positive effect on purchasing decisions. This study aims to determine the effect of brand image,